2015
DOI: 10.1115/1.4029614
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Multiple-Injection Dry Low-NOx Combustors on Hydrogen-Rich Syngas Fuel in an IGCC Pilot Plant

Abstract: The successful development of coal-based integrated gasification combined cycle (IGCC) technology requires gas turbines capable of achieving the dry low nitrogen oxides (NOx) combustion of hydrogen-rich syngas fuels for low emissions and high plant efficiency. Mitsubishi Hitachi Power Systems, Ltd. (MHPS) has been developing a “multiple-injection burner” to achieve the dry low-NOx (DLN) combustion of hydrogen-rich syngas fuels. The purposes of this paper are to present the test results of a multican combustor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 3 publications
1
22
0
Order By: Relevance
“…Yoshimura et al [65] indicated that multipoint technology not only has the capacity of NOx reduction but also prevents flashbacks, hence hydrogen addition can be done in this concept. This is also confirmed from other research studies such as York et al [66], Asai [67] and Marek et al [68]. In the present study, though the injector design is generic and has a wide range of applications, its main purpose is for the applications where the required pressure drop across the atomizer is low.…”
Section: Lean Direct Injection (Ldi) Combustorsupporting
confidence: 89%
“…Yoshimura et al [65] indicated that multipoint technology not only has the capacity of NOx reduction but also prevents flashbacks, hence hydrogen addition can be done in this concept. This is also confirmed from other research studies such as York et al [66], Asai [67] and Marek et al [68]. In the present study, though the injector design is generic and has a wide range of applications, its main purpose is for the applications where the required pressure drop across the atomizer is low.…”
Section: Lean Direct Injection (Ldi) Combustorsupporting
confidence: 89%
“…[213][214][215] The MM technology is based on the concept of mixing of fuel and oxidizer at the microscale. [213][214][215] The MM technology is based on the concept of mixing of fuel and oxidizer at the microscale.…”
Section: Combustion Technologymentioning
confidence: 99%
“…MM burners are a successful emerging LPM combustion technology that is already implemented on the utility scale (eg, General Electric's F-class gas turbines). [213][214][215] The MM technology is based on the concept of mixing of fuel and oxidizer at the microscale. A MM consists of a two-dimensional array of straight, parallel, equallyspaced tubes (each of a diameter of few millimeters) welded to two faceplates; one forms the inlet section of the burner, while the other forms the exit section.…”
Section: Combustion Technologymentioning
confidence: 99%
“…One opportunity to retrieve the energy is the direct combustion of the H 2 . Several projects on the combustion of hydrogen-rich fuels were initiated in the last years in industry [4][5][6][7][8][9]. However, these technologies still produce NO x and CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%